Analysis of the risk of malignancy associated with the basaloid and oncocytic subtypes of the salivary gland neoplasm of unknown malignant potential (SUMP) category in the Milan system. Issue 8 (31st March 2021) - Manucha, Varsha; Gonzalez, Maria F.; Akhtar, Israh
Abstract : BACKGROUND: The salivary gland neoplasm of unknown malignant potential (SUMP) category reflects the cytomorphologic overlap and complexity of reporting salivary gland cytology in the Milan system. It includes neoplasms for which a diagnosis of a specific entity cannot be made and, more importantly, for which a carcinoma cannot be entirely excluded. For risk stratification, the subcategorization of SUMP based on the predominant cell type is recommended. This study was aimed at evaluating the risk of neoplasm (RON) and the risk of malignancy (ROM) of the basaloid and oncocytic subtypes of the SUMP category. METHODS: A retrospective analysis of 482 salivary gland fine‐needle aspirations from 2012 to 2019 resulted in 48 SUMP cases. The cytology of these cases was reviewed and reclassified as the basaloid or oncocytic subtype. Surgical follow‐up was available for 36 cases. The RON and ROM for each subtype were calculated. RESULTS: The RON and ROM were 100% and 23%, respectively, for monomorphic basaloid tumors and 88% and 58.8%, respectively, for monomorphic oncocytic tumors. The ROM for basaloid tumors was 8.3% without matrix/with minimal matrix and 60% with an nonfibrillary matrix. The ROM for oncocytic tumors was 50% without a cystic background and 60% with a cystic or mucinous background. The difference was not statistically significant for either of the subgroups. CONCLUSIONS: Even though statistically not significant in our study, the differential ROMs within the oncocytic and basaloid subgroups help in the risk stratification of SUMP cases. Further subcategorization based on the stroma and background helps in limiting the differential diagnosis but does not necessarily add to the value of the risk stratification. Abstract : Although the basaloid and oncocytic subtypes of the salivary gland neoplasm of unknown malignant potential category of salivary gland neoplasms have different risks of malignancy, further risk stratification based on stroma and background is challenging.